Confederates in the attic : dispatches from the unfinished Civil War - Horwitz, Tony, 1958-2019. (New York : Vintage Books, 1998)
"When prize-winning war correspondent Tony Horwitz leaves the battlefields of Bosnia and the Middle East for a peaceful corner of the Blue Ridge Mountains, he thinks he's put war zones behind him. But awakened one morning by the crackle of musket fire, Horwitz starts filing front-line dispatches again this time from a war close to home, and to his own heart. Propelled by his boyhood passion for the Civil War, Horwitz embarks on a search for places and people still held in thrall by America's greatest conflict. The result is an adventure into the soul of the unvanquished South, where the ghosts of the Lost Cause are resurrected through ritual and remembrance. In Virginia, Horwitz joins a band of 'hardcore' reenactors who crash-diet to achieve the hollow-eyed look of starved Confederates; in Kentucky, he witnesses Klan rallies and calls for race war sparked by the killing of a white man who brandishes a rebel flag; at Andersonville, he finds that the prison's commander, executed as a war criminal, is now exalted as a martyr and hero; and in the book's climax, Horwitz takes a marathon trek from Antietam to Gettysburg to Appomattox in the company of Robert Lee Hodge, an eccentric pilgrim who dubs their odyssey the 'Civil Wargasm.' Written with Horwitz's signature blend of humor, history, and hard-nosed journalism, Confederates in the Attic brings alive old battlefields and new ones 'classrooms, courts, country bars' where the past and the present collide, often in explosive ways. Poignant and picaresque, haunting and hilarious, it speaks to anyone who has ever felt drawn to the mythic South and to the dark romance of the Civil War." -- Publisher's description.
Originally published: New York: Pantheon Books, 1998.
Includes index.
Keywords: Horwitz, Tony, -- 1958-2019 -- Travel -- Southern States; United States -- History -- Civil War, 1861-1865 -- Influence